Studi Komparatif Fungsi Pendidikan Agama Islam di Sekolah Negeri dan Swasta - Abd Mannan; Trisna Rukhmana; Al Ikhlas; Ahmad. Aziz Masyhadi; H. Mardiah; Nila Mayasari (Journal on Education, 2024)
Islamic religious education has a significant role in shaping the character and morality of Muslim individuals. In the context of formal education, both public and private schools in Indonesia, Islamic religious education is an integral part of the curriculum. This study aims to conduct a comparative analysis of the function of Islamic religious education in public and private schools. A comparative approach is used to understand the differences and similarities in the approach to Islamic religious education in the two types of schools, focusing on aspects such as curriculum, teaching methods, student acceptance and learning outcomes. The research was carried out through interviews, observations and document analysis of the schools that were the research samples. The results of the analysis show that there are significant differences in the approach to Islamic religious education in public and private schools, including in terms of curriculum, teaching methods and student learning outcomes. However, both types of schools also have similarities in their efforts to provide quality Islamic religious education. These findings provide valuable insight for the future development of Islamic religious education, both in public and private schools, in order to increase the effectiveness and relevance of Islamic religious education in shaping the character and morality of the young Muslim generation.